Extracellular vesicles in disorders of hemostasis following traumatic brain injury - Mc Mahon, Aisling; Weiss, Luisa; Bennett, Kathleen; Curley, Ger; Ní Ainle, Fionnuala; Maguire, Patricia (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI) is a global health priority. In addition to being the leading cause of trauma related death, TBI can result in long-term disability and loss of health. Disorders of haemostasis are common despite the absence of some of the traditional risk factors for coagulopathy following trauma. Similar to trauma induced coagulopathy, this manifests with a biphasic response consisting of an early hypocoagulable phase and delayed hypercoagulable state. This coagulopathy is clinically significant and associated with increased rates of haemorrhagic expansion, disability and death. The pathophysiology of TBI-induced coagulopathy is complex but there is biologic plausibility and emerging evidence to suggest that extracellular vesicles (EVs) have a role to play. TBI and damage to the blood brain barrier result in release of brain-derived EVs that contain tissue factor and phosphatidylserine on their surface. This provides a platform on which coagulation can occur. Preclinical animal models have shown that an early rapid release of EVs results in overwhelming activation of coagulation resulting in a consumptive coagulopathy. This phenomenon can be attenuated with administration of substances to promote EV clearance and block their effects. Small clinical studies have demonstrated elevated levels of procoagulant EVs in patients with TBI correlating with clinical outcome. EVs represent a promising opportunity for use as minimally invasive biomarkers and potential therapeutic targets for TBI patients. However, additional research is necessary to bridge the gap between their potential and practical application in clinical settings.